2016
DOI: 10.1111/exd.13081
|View full text |Cite
|
Sign up to set email alerts
|

The continued use of sunscreen prevents the development of actinic keratosis in aged Japanese subjects

Abstract: It is well known that the trigger for actinic keratosis (AK) mainly depends on UV exposure. We evaluated the effects of long-term use of sunscreen on the histopathological and dermoscopic changes of AK in aged patients. Eighteen months use of sunscreen produced no change in the number of actinic keratoses or the advancement of histological grade. Although a significant decrease was not observed in the number of positive cells of p53, Ki-67 and COX-2 of the subjects who used sunscreen for 18 months, the downwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…47,48 However, in our previous study, no statistically significant difference was observed in the number of AK lesions before and after application of sunscreen, and the number of AK lesions decreased in only a small proportion of the subjects. 12 It is reported that more marked wrinkle formation and skin sagging are observed in Caucasian females compared to similar aged Japanese females. 8 When compared to Caucasians, Japanese are thought to have a lower sensitivity to UV and less susceptibility to photocarcinogenesis and photoaging because they have a lower incidence of AK and SCC, and characteristics of lower risk factors for AK such as lower skin phototypes or darker eye colors.…”
Section: Susceptibility To Photoaging In Japanese Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…47,48 However, in our previous study, no statistically significant difference was observed in the number of AK lesions before and after application of sunscreen, and the number of AK lesions decreased in only a small proportion of the subjects. 12 It is reported that more marked wrinkle formation and skin sagging are observed in Caucasian females compared to similar aged Japanese females. 8 When compared to Caucasians, Japanese are thought to have a lower sensitivity to UV and less susceptibility to photocarcinogenesis and photoaging because they have a lower incidence of AK and SCC, and characteristics of lower risk factors for AK such as lower skin phototypes or darker eye colors.…”
Section: Susceptibility To Photoaging In Japanese Populationmentioning
confidence: 99%
“…These results indicated the preventive effect of sunscreen against AK and SCC in Japanese people. 12 In Caucasians, many reports demonstrate the disappearance of AK after long-term application of sunscreen. 47,48 However, in our previous study, no statistically significant difference was observed in the number of AK lesions before and after application of sunscreen, and the number of AK lesions decreased in only a small proportion of the subjects.…”
Section: Susceptibility To Photoaging In Japanese Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used RNA-seq to investigate the psoriasiform phenotype that develops following topical Aldara (5% IMQ) treatment in male and female mice of seven laboratory mouse strains (C57BL/6 J (B6), BALB/cJ, CD1, DBA/1 J, FVB/NJ, 129X1/SvJ, and MOLF/EiJ) [19]. The IMQ psoriasiform phenotype has previously been evaluated using microarrays [2, 2022], but to our knowledge has not yet been evaluated by RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that continuous application of sunscreen is effective in suppressing AK progression and generation, and for the prevention of SCC development. 12 …”
Section: Introductionmentioning
confidence: 99%